Influence of Product Quality and Brand Image on Purchase Decision of Chevrolet Automobile Product - Magdalena; Hendy Tannady; Siti Nurjanah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to find out whether the product quality and brand image of Chevrolet products affect purchasing decisions. This type of research uses a quantitative approach using the purposive sample method, with the criteria of having a Chevrolet Trailblazer car. In this study, there are 2 variables studied, namely Product Quality and Brand Image. The sample of this study was taken from the Indonesian Trailblazer group with 140 respondents, using data analysis techniques of Classical Assumptions, Normality, Multicollinearity, Heteroscedasticity and Multiple Linear Regression. The result of this analysis is that product quality and brand image can influence purchasing decisions from the Chevrolet Trailblazer.